The gauss law operator algebra and double commutators in chiral gauge theories - Pawlowski, Jan M. (Arxiv, 1997)
We calculate within an algebraic Bjorken-Johnson-Low (BJL) method anomalous Schwinger terms of fermionic currents and the Gauss law operator in chiral gauge theories. The current algebra is known to violate the Jacobi identity in an iterative computation. Our method takes the subtleties of the equal-time limit into account and leads to an algebra that fulfills the Jacobi identity. The non-iterative terms appearing in the double commutators can be traced back directly to the projective representation of the gauge group.